Effects of dietary linolenic acid to linoleic acid ratio on growth performance, proximate composition and fatty acid contents of pacu (Piaractus mesopotamicus) - Cyrino, José Eurico Possebon; Kleber Lorenz, Evandro; Barone, Rafael Simões Coelho; Cortegano, Carlos Andre Amaringo; Gonçalves, Lígia Uribe (Aquaculture Research, 2021)
Freshwater fish have the ability to convert linolenic acid (LNA) into EPA and DHA and linoleic acid (LA) into ARA from elongation and desaturation process. The optimal LNA/LA in aquafeeds formulated with vegetable oils can improve the n-3/n-6 ratio in fish flesh. This study aimed at determining the effects of varying dietary LNA/LA ratios on the growth and proximate composition and fatty acids content in the flesh of pacu, Piaractus mesopotamicus. Juvenile pacu (110 ± 1.6 g) were fed for 60 days with diets containing varying levels of sunflower (SO) and linseed (LO) oils (100SO; 75SO:25LO; 50SO:50LO; 25SO:75LO; 100LO), and performance and proximate composition and fatty acids contents of fish flesh were analysed. Experimental diets did not affect fish growth performance. Although the EPA and DHA content were lower in the fish fed the experimental diets than control diet (fish oil), the complete replacement of fish oil by an approximate proportion of 12SO:88LO, in an optimal LNA/LA ratio (2.2–2.4), represents an improvement in nutraceutical quality of the flesh for human consumption. Fish-fed ideal LNA/LA ratio diets have higher total n-3 fatty acids contents, and higher n-3/n-6 and EPA/ARA ratios, without hampering fish performance and flesh proximate composition. © 2021 John Wiley & Sons Ltd
Keywords: Eicosapentaenoic acid; Neotropical fish